Fungemia by yeasts in Brazil: occurrence and phenotypic study of strains isolated at the Public Hospital, Botucatu, São Paulo - Ruiz, L. S.; Sugizaki, M. F.; Montelli, A. C.; Matsumoto, F. E.; Pires, MFC; Da Silva, BCM; Silva, E. H.; Gandra, R. F.; da Silva, E. G.; Auler, M. E.; Paula, C. R. (Masson Editeur, 2005)
Objective. - In this study strains of yeasts isolated from the blood of human patients were analyzed taxonomically, their virulence factors were determined and compared, and phenotypic markers were used to compare the samples with respect to phenotypic differences across the range of patients as well as between samples isotated from the same patient.Methods. - the study involved a total of 75 strains of yeast isolated from the blood of in-patients of the Public Hospital, Botucatu, S (a) over tildeo Paulo, Brazil, with a clinical profile of fungemia. The hospital wards with the largest number of fungemias were neonatal intensive care units (ICUs) (32%) followed by gastric surgery (13.4%) and pediatric wards (10.7%). After identification, the samples were analyzed for the production of phospholipase and proteinase enzymes, and biotyped according to their susceptibility to killer toxins.Results. - the most frequent species found was Candida albicans (38.7%) followed by C. parapsilosis (30.7%). In terms of enzyme production, 98.7% of the 75 samples of yeast presented a strongly positive activity for proteinase; however, 78.7% did not present any phospholipasic activity. Six different biotypes were identified, the most frequent being 511 and 888.Conclusion. In association with phenotypic methods, genetic analyses should also be made of the samples under study to help in the rational development of a wider range of preventive measures and better control of hospital-contracted infections. (c) 2005 Published by Elsevier SAS.
Keywords: Candida spp; fungemia; exoenzymes; killer toxins